Igrejas evangélicas inclusivas das cidades de São Paulo e Guarulhos: um estudo psicopolítico das igrejas vistas por seus pastores - Rodrigues, Eduardo Lima (2009)
The purpose of this research was to investigate what are the social representation leaders of Inclusive Churches about their churches and the relation of these with Social Movements. The inclusive churches are churches that, on the contrary to the conventional churches, do not condemn the homosexuality of their members. There are in São Paulo City three inclusive churches: Igreja da Comunidade Metropolitana, Comunidade Cristã Nova Esperança, Igreja Cristã Evangelho Para Todos and in Guarulhos City there is one branch of Comunidade Cristã Nova Esperança. In order to understand the social representations of these leaders we attended cults and the participation of these churches on the Marcha Para Jesus, Parada do Orgulho GLBT and Seminário de Inter-religiosidade e Diversidade Sexual. We visited the churches and interviewed three men pastors and a woman pastor. After collecting the data, their discourses are divided into thematic nucleus. In order to analyze the material, we used the Social Representation Theory, elaborated by Serge Moscovici. The data point out the leaders conceptions about their churches and about the relation of these with Social Movements. The churches are wiewed like a place that the homosexual can have a new reunion with God. The Social Movements are considered something very important by the leaders although there is not a big integration behind the churches and Social Movements